Esej in književnost v drugi polovici dvajsetega stoletja - Štuhec, Miran (Slavistična revija, 2003)
The literary essay is the largest representative of Slovene essay writing. The interest of the writers was focused on literary works, their stylistic and ideal parameters, it reflected on the writers and their literary opuses, discussed ontological questions of literarure, etc. Some, particularly younger writers and essayists of the middle generation, placed literature in the realm of intertextual relations and in cultural, social, historical, as well as political and economic contexts. Taking into account that the authors belonged to various world-views, political, philosophical, and ideological circles, one must conclude that the literary essay thoroughly broadened and deepened the knowledge of (Slovene) literature
Keywords: esej; esejistika; history of literature; kritika; literarna zgodovina; Slovene literature; slovenska književnost